A qualitative study into the extent to which the marketing strategies of online sports betting companies affect consumer behaviours and behavioural intentions. - Dootson, Joseph (2022)
The main aim of this study is to investigate the extent of the effect that the marketing strategies of online sports betting companies have on the behaviours and behavioural intentions of their consumers. This study makes use of the theory of planned behaviour as a theoretical framework to guide the scope of the study and provide structure to the investigation.